A reliable and economically feasible automatic meter reading system using power line distribution network - Moghavvemi, M.; Tan, S.Y.; Wong, S.K. (2005)
Automatic Meter Reading (AMR) is the remote collection of consumption data from customer's utility meters over telecommunications, radio, power line and other links. AMR provides water, electric and gas utility-service companies the opportunities to streamline metering, billing and collection activities, increase operational efficiency and improve customer service. Utility company uses technologies that were developed several decades ago with the majority of the meters being read visually. With manual readings, considerable time is used to physically check out each unit. AMR becomes a viable option to overcome this problem of time wastage to obtain the meter readings. There are many different forms of communication links that can be utilized as the communication medium in an AMR system. One such link is the power line carrier or PLC. The advantages of using the PLC as the communication medium are readily apparent since the power line network is the property of the utility company and its infrastructure is already there. However, power lines are never meant for communication and creates much noise and therefore, various modifications has to be made to make the PLC suitable to be the AMR communication channel. The AMR system consists of three major components: the meter interface module, communications system, and data concentrator. This paper details a feasibility study on the creation of a robust bi-directional/two-way communication system between an electricity meter and a distant control unit (data concentrator) over the low voltage (LV) distribution grid. Basic functions of the AMR system include the provision for remote connection and disconnection of meter and fraud detection features at both the meter interface and the data concentrator. As a support system to the entire AMR, batteries are utilized. They are especially important in the cases of power failures. Lithium-ion batteries are the type of batteries that are used as these batteries tend to last longer than most other batteries. The main advantage of this system is that it is a low cost system that produces very encouraging results and it can be implemented upon existing electro-mechanical meters without the need of purchasing new meters. With many existing meters being the electro-mechanical meters, the need for a high-cost, large-scale implementation of new electronic device meters to enable implementation of the AMR system is unnecessary. The cost of implementation is low and the benefits, especially economically, that it brings to the utility company are immense.